Effect of sources of coconut water and acidulants on physico chemical properties of nata-de-coco - Thankappan, Geethumol; Anitha, P. (Journal of Tropical Agriculture, 2019)
A study was conducted to find out the effect of sources of coconut water and acidulants on the physicochemical properties of nata-de-coco (nata). Coconut water from WCT and CDO showed significant effect on the physico-chemical properties of nata. Days to nata formation (17.25), thickness of nata (8.62 mm), weight of nata (378.12 g), TSS (8.720 Brix) and total sugars (1.20g 100g-1) were significantly high when coconut water from CDO was used. However, protein (0.12%) was significantly high when nut water from WCT was used. Fibre (%) and moisture (%) were not influenced by sources of coconut water. Acidulants such as acetic acid and bilimbi juice were on par in their effect on physico-chemical properties of nata. Sugar content of the substrate, measured as total soluble solids (TSS° Brix) is the most important factor which determines the yield of nata.